Excitation and electroporation in genetically engineered excitable S-HEK cells exposed to electric pulses of different durations - Tina Batista Napotnik; Tina Cimperman; Lea Rems (Scientific Reports)
Abstract Electroporation affects action potential generation in excitable cells such as nerve, muscle and cardiac cells. Since electroporation-based treatments use different pulse protocols, we investigated how electric pulses of different duration (from 500 ns to 1 ms) trigger action potentials and cause electroporation in genetically engineered cultured excitable cell model. Transmembrane voltage was monitored using a fluorescent potentiometric probe and fluorescence microscopy. We triggered similar responses in these cells using electric pulses of all pulse durations. At lower electric fields, we stimulated action potentials and at higher electric fields, electroporation occurred: the action potentials were gradually prolonged and eventually, ended up in sustained depolarization. For shorter pulses, higher electric fields had to be used to achieve the same effect. However, the shape of the action potential was affected by pulse duration. With shorter pulses (500 ns–10 µs), the action potentials were much longer already at the excitation thresholds, due to more prominent effect of electroporation, compared to longer pulses (e.g., 1 ms) where action potentials were triggered by classical electrostimulation (i.e., excitation) without electroporation. Moreover, we detected a complex, biphasic intracellular calcium response in excitable S-HEK cells that was absent in non-excitable NS-HEK version of these cells.